Association of vitamin D receptor gene polymorphisms with osteosarcoma risk and prognosis - Kurucu, Nilgun (J Bone Oncol, 2018)
OBJECTIVE: Through its receptor (VDR), vitamin D(3) plays an important role in a wide variety of cellular processes. Polymorphisms in VDR gene have been linked to risk of various cancers and their prognoses. We conducted a case-control study to analyze he relationship of VDR gene polymorphisms with the occurrence and prognosis of osteosarcoma. METHODS: Fifty-eight osteosarcoma patients and 75 healthy controls were included in the study. Single nucleotide change polymorphisms (SNPs) in Cdx2, FokI, BsmI, ApaI and TaqI regions of VDR gene were examined with SNaPshot mini-sequencing technique. Allele and genotype frequencies in patients and controls were compared. The association of polymorphic genotypes with osteosarcoma was evaluated. The relationship of the presence of polymorphism to prognostic parameters and survival rates were also analyzed. RESULTS: Allele and genotype frequencies of Cdx2, FokI, BsmI, ApaI and TaqI regions in VDR gene were found to be similar in patients and controls. Polymorphisms in these regions were not associated with osteosarcoma risk. In patients having Cdx2 polymorphic allele, tumor volume was greater (p:0.041), metastasis was more common (p:0.042) and histopathological response to chemotherapy was worse (p:0.044). Good histopathological response was significantly higher in patients with BsmI homozygous polymorphism (p:0.037). In the presence of heterozygous Cdx2 and homozygous a higher three-year overall survival rate was found, while there was a higher event-free survival rate in patients with ApaI polymorphisms. CONCLUSION: Our results suggested that although polymorphisms of VDR gene are not related to the development of osteosarcoma, they may be important for prognosis. Understanding the effect of VDR polymorphisms on osteosarcoma will be important in identifying new prognostic parameters and new targets for treatment.